USING SHOW AND TELL METHOD IN IMPROVING THE STUDENTS’ VOCABULARY MASTERY TO THE EIGHTH GRADE STUDENTS OF SMP NEGERI 1 BATANG NATAL - Siti Meutia Sari; Tinur Rahmawati Harahap; Parpol Parpol; Elissa Evawani Tambunan (English Department, University of Riau Kepulauan, Batam,Indonesia, 2021)
The purpose of this study is to knowwhether using Show and tell method in teaching can improve the students’ vocabulary mastery or not. This technique can improve and increase student’s ability to learn the target language and make them enjoy in the teaching learning process. It supposes to motivate students to learn English actively by using show and tell method. Students also are encouraged to get long memorizing of the words and their meaning. The method that is used in this research is the classroom action research.For getting the needed data, the writer applies the library and field research. The library research is applied based on the needs of the books as the sources of theories and informations, and the field research is applied based on the need of data from the field, in this case from the SMP Negeri 1 Batang Natal. And as the instrument for collecting the data the writer uses the written test. To the result of implementing classroom action research inthe eleventh grade students of SMP Negeri 1 Batang Natal in 2020 - 2021 academic year, it showed a great improvement in which the mean score of students in pretest is 61.03, whereas in post test 1 is 68.60 and in post test 2 are80.37. Besides, the students’ score percentage in the pretest is 8.82%, from posttest 1 is 31.69 % and 82.35 % from post test of students who have passed the KKM.Next, the result of the students’ score improvement from pretest to posttest 1is 8.82 %, and from pretest to posttest 2 is 31.69%. The percentage got from the result of post – test 2 has achieved the criteria of successSo that, it can be concluded thatthere is a significant improvement of the students’ vocabulary mastery after they are taught by using Show and tell method”.And it can be stated that the formulated hypothesis is accepted.